2023
DOI: 10.31234/osf.io/t8h6a
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lost in time and space? Multisensory processing of peripersonal space and time perception in Depersonalisation

Abstract: Perception of one’s self and body in time and space are fundamental aspects of self-consciousness. It scaffolds our subjective experience of being present, in the here and now, a vital condition for our survival and wellbeing. Depersonalisation (DP) is characterized by distressing feeling of being ‘spaced out’, detached from one’s self, body and the world, as well as atypical ‘flat’ time perception. Using a multisensory audio-tactile paradigm, we have conducted a study looking at the effect of DP experiences o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…processing of external sensory inputs) and interoceptive (i.e. processing of internal sensory inputs) integration seems to be involved in bodily self-awareness (Craig, 2009;Tsakiris et al, 2011; see Park and Blanke, 2019 for a review), and a consistent body of literature pointing to the links between sensory disintegration and depersonalisation (Sel et al 2017, Heydrich et al 2018Adler et al 2016;Ferroni et al, 2023; see also Salami et al, 2020). A recent study by Arslanova et al (2023) observed cardiac fluctuations derived from emotionally charged visual stimuli, causing cardiacled time distortions.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…processing of external sensory inputs) and interoceptive (i.e. processing of internal sensory inputs) integration seems to be involved in bodily self-awareness (Craig, 2009;Tsakiris et al, 2011; see Park and Blanke, 2019 for a review), and a consistent body of literature pointing to the links between sensory disintegration and depersonalisation (Sel et al 2017, Heydrich et al 2018Adler et al 2016;Ferroni et al, 2023; see also Salami et al, 2020). A recent study by Arslanova et al (2023) observed cardiac fluctuations derived from emotionally charged visual stimuli, causing cardiacled time distortions.…”
Section: Discussionmentioning
confidence: 98%
“…For example, depression, rumination are usually associated with a past-oriented focus (Wang et al, 2021), while anxiety is related to problems with future time perspective (Kooij et al, 2018). Alterations in time perception investigated in terms of dissociative disorders also suggest deficits in temporal processing and perceptual abilities (Ferroni et al, 2023;Hart & Steele, 1997;Kent et al, 2022;Spiegel & Cardeña, 1991). Depersonalisation (DP) is a type of dissociative disorder that refers to the experience of feeling detached from one's self, body, and emotions (Sierra & Berrios, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Self, Space and Time" Questionnaire (SST) Additionally, all participants completed the "Self, Space and Time" Questionnaire (SST) composed of 14 items, scored on 5-point Likert scales (see Supplementary Material -I). The SST was developed by one of us (AC) to explore in depth the link between DP and altered spatiotemporal perception (Ferroni et al, 2023) in relation to the bodily self. T-test comparisons were conducted across HIGH DP and LOW DP participants, revealing signi cant differences across sample -apart for items 2, 3 and 4 (see Table D in Supplementary Material).…”
Section: Methodsmentioning
confidence: 99%
“…The potential impairment in updating one's self-face image may also have fundamental links with subjective time perception, a process that appears to also be atypical in individuals with high DP who often report a lack of plot or narrative (Ciaunica et al, 2021) making them feel 'stuck in time' (Almeida et al in prep; Ciaunica et al in prep). For example, a recent study (Ferroni et al, 2023) used the Mental Time Travel task (MTT: Arzy, Molnar-Szakacs, & Blanke, 2008) to measure individuals' capacity of constructing one's own temporal perspective toward the past and the future by referring to personal experience. The authors found poorer performance in locating events in time relative to their present reference point in people with high DP.…”
Section: Visualizable At a Group Level?mentioning
confidence: 99%